The Effect Of Internship Experience On Job Readiness With Self-Efficacy As Moderation - Anggraeni, Cicilia Dena Anggraeni; Nurhasanah, Siti; Arifiani, Ratya Shafira (Universitas Muhammadiyah Malang, 2024)
The purpose of this study is to identify and analyze apprenticeship experience, work readiness and self-efficacy, the effect of apprenticeship experience on work readiness, analyze apprenticeship experience on work readiness with self-efficacy as moderation. This type of research uses explanatory research with a quantitative approach. The population and sample in this study were all 2019 class management students who took part in the internship as many as 98 students. The sampling technique uses saturated or census sampling. Collecting data using a questionnaire technique (questionnaire) and interviews. Data analysis used simple regression analysis with SPSS 29 software. The results showed that apprenticeship experience was at a good level, job readiness was at a high level and self-efficacy showed a high level. There is a positive and significant influence between the effect of apprenticeship experience on work readiness, self-efficacy cannot moderate the effect of apprenticeship experience on work readiness.